Ответы и объяснения

  • Участник Знаний
2014-02-09T20:18:24+04:00
1) = ( 10 - ( 3A + 7Y ) ) * ( 10 + (3A + 7Y)) = ( 10 - 3A - 7Y) * ( 10 + 3A + 7Y )
2) = ( M^3N ) ^2 - ( M - N )^2 = ( M^3N - ( M - N ) ) * ( M^3N + ( M - N )) =
= ( M^3N - M + N ) * ( M^3N + M - N ) 
3) = ( 3XY^2)^2 - ( A - B)^2 = ( ( 3XY^2) - ( A - B )) * ( ( 3XY^2) + ( A - B )) = 
= ( 3XY^2 - A + B ) * ( 3XY^2 + A - B ) 
??????????????????????
Комментарий удален
У меня правильное решение во всех трёх примерах.
Комментарий удален
Комментарий удален